Systematic Review of Music Therapy and Musical Interventions for Patients with Moderate and Severe Mental Disorders - Cassola, Eduardo Gabriel [UNESP]; Santos, Lucas Cardoso dos; Ferreira, Maria Solange de Castro [UNESP]; Correa Barbosa, Guilherme [UNESP]; Betini, Marluci [UNESP]; Domingos, Thiago da Silva (SAGE Publications, 2024)
Objective: This systematic review aims to assess the impact of music therapy and musical interventions on neuropsychiatric outcomes among patients with moderate and severe mental disorders, in comparison with conventional treatment in isolation. Methods: The review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A comprehensive search was conducted on November 16, 2021, using the following databases and search interfaces: Cumulative Index to Nursing and Allied Health Literature, Embase, SCOPUS, Web of Science; PubMed, PsycINFO, Literatura Latino-Americana e do Caribe em Ciências da Saúde, and Scientific Electronic Library Online. Two authors independently assessed the studies for inclusion criteria, extracted the data, and evaluated the quality of the included studies using critical appraisal tools. Results: In total, 17 studies were included, 9 of which were randomized controlled trials. The experimental studies involved 5,082 adult and elderly patients. The most prevalent symptoms assessed in the studies were anxiety, depression, and positive and negative symptoms of psychotic disorders. Music interventions were predominantly conducted by music therapists and nurses, providing passive interventions with the selection of musical repertoire by therapists and patients. The frequency with which musical interventions occurred varied greatly in terms of session duration, number of times per week, and number of times during the day. The identified study designs included clinical and quasi-experimental studies. In terms of methodological quality, clinical studies showed weaknesses regarding deviations from intended interventions. Conclusion: The effectiveness of music therapy and musical interventions for neuropsychiatric symptoms in patients with moderate and severe mental disorders was evident in quasi-experimental and clinical studies with satisfactory methodological quality. Musical interventions, in various forms of application, represent an interdisciplinary therapeutic tool that complements and enhances conventional treatment. Unlike conventional treatments, the immersive and integrative nature of music interventions allows access to both intrapersonal and interpersonal dimensions during periods of psychic suffering. These findings highlight the importance of researchers addressing methodological limitations, such as deviations from intended interventions, and advocate for the expansion the use of music in community treatment settings.
Keywords: anxiety; depression; music therapy; psychotropics; severe mental disorders